STUDY OF THE IMPACT OF FAMILY BACKGROUND OF ADOLESCENTS ON THEIR INTERNAL AND EXTERNAL PERSONALITY AND EDUCATIONAL ACHIEVEMENT - Kashyap, Reena; Sharma, Kavita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A child is helpless at the time of birth, the task of strengthening that helpless child is done by his parents. Parents are the trainers and helpers of the child. If the environment of the house is favorable to the child, then the parents are successful in shaping the child. According to Prof. Lister Smith - A school should not only be a place to impart theoretical knowledge, but a school should be a place to impart permanent knowledge to the children and the environment of the school should enhance the teaching ability of the teachers and help in the development of the personality of the learners. Students are provided a strong foundation in the family by the parents. And on this foundation, the educational achievement of the students is enhanced in the form of a palace in the schools and the student in the form of a palace is decorated with battlements by the people. By acquiring knowledge, a student who was helpless, weak at the time of birth and his mind was like a blank slate, gets educated and achieves the peak of achievements due to which he gets the position of an officer, this is his educational achievement.